Pengawasan Masyarakat dalam Menjaga Kelestarian Ekosistem Sungai Rasau di Desa Petak Bahandang Kecamatan Tasik Payawan Kabupaten Katingan - Nurhasanah Nurhasanah; Ariyanto Ariyanto (Pencerah Publik, 2017)
The river is one part that cannot be separated from our daily lives. The river in Katingan Regency is used by the community for various activities, including transportation, MCK (bathing, washing, toilet), and their daily economic activities. However, the reality in the field shows that the water quality in the Rasau River is not suitable for use by the people, the turbid water makes them have to think twice to use it. The purpose of this study was to explain and describe Community Supervision in Maintaining the Conservation of Sungai Rasau Ecosystem in Petak Bahandang Village, Tasik Payawan District, Katingan District, Central Kalimantan Province. This research uses qualitative research methods, which are intended to develop concepts, gather facts that are supported and supported by real data. Sources of data in this study are the employees of the Petak Bahandang Village, the Petak Bahandang Village community, and documents relating to Community Monitoring in Maintaining the Conservation of Sungai Rasau Ecosystem in Petak Bahandang Village, Tasik Payawan District, Katingan District, Central Kalimantan. Data collection techniques are observation, documentation and in-depth interviews. From the results of the study that Community Monitoring in Maintaining the Conservation of Sungai Rasau Ecosystem in Petak Bahandang Village, Tasik Payawan Subdistrict, Katingan District, Central Kalimantan Province is still low due to several factors, work, education, and leadership. Especially in planning, supervision, and maintenance, the community still lacks participation in it.